Swiss Diagnosis Related Groups: A prospective study in rehabilitation comparing outcome before and after its introduction into acute health care (Swiss Medical Weekly, 2014)
OBJECTIVE: To compare general health and the health-related quality of life of patients admitted to inpatient rehabilitation after a stay in an acute hospital before and after the introduction of Swiss Diagnosis Related Groups (SwissDRG). METHODS: Consecutively referred patients with disorders of the lower extremities (LEX) or lumbar spine (LS) were evaluated by standardised outcome assessment instruments and for various co-factors. State (at entry to rehabilitation) and change of health (between entry and discharge from rehabilitation) were then compared between the cohorts before and after introduction of SwissDRG. RESULTS: In LEX (n = 234), state of health, measured by the instruments’ scores at entry, was not significantly different before and after SwissDRG, except for emotional role (worse state after SwissDRG, p = 0.021). These results were consistent for the LS group (n = 161). Change of health from entry to dismissal was comparable before and after DRG in the LEX group, whereas in the LS group, improvements after SwissDRG were significantly smaller in physical role (p = 0.042), bodily pain (p = 0.012) and physical component summary (p = 0.009) than before SwissDRG. Duration of stay in an acute hospital and duration of stay in the rehabilitation clinic were comparable before and after SwissDRG in both groups. CONCLUSIONS: While state of health was comparable in both diagnostic groups, some dimensions in the LS group revealed lesser improvements after introduction of SwissDRG compared to before. In analogy to long-term observations after the introduction of DRG in Germany, it is possible that greater differences will also be identified in Switzerland by future studies.